Impact of Customer Relationship Marketing on Customer Loyalty - A comparative study between state banks and private banks in Northern Region of Sri Lanka - Jude Leon, S.A.; Pathmini, M.G.S. (Faculty of Arts and Culture South Eastern University of Sri Lanka., 2019)
In recent years, there is a growing interest in achieving customer loyalty in general but specially in the service sector. Customer relationship marketing (CRM) becomes one of the powerful tools to make it true. This study examines the relationship between CRM and customer loyalty as a comparative study between State Banks and Private Banks in Northern Region of Sri Lanka. The Problem of this study is to test how CRM has impact on customer satisfaction and customer loyalty in Sri Lankan banking industry. Trust, commitment, communication, conflict handling and empathy have been used as independent variables of the study under the main construct of CRM and Customer Loyalty as Dependent Variable and Customer Satisfaction as mediating variable in this study. This study is a deductive one as it tries to find out the relationship among CRM and customer satisfaction and customer loyalty. It is also a positivist approach as it is a qualitative approach using structured questionnaires. It is a cross sectional research as it compares different population groups at a single point in time as comparing state bank customers and private bank customers. For this study, data were collected by using the primary data as well as secondary data. Sample size is being selected under two stages considering organizational level (30 bank branches) and individual level (300 customers) by using stratified sampling. Both descriptive statistics and inferential statistics are used to analyze the data. Findings of the study indicated that, there is a significant relationship between CRM and customer loyalty. And also, it shows that, Trust, commitment, communication, conflict handling and empathy have significant impact on customer loyalty.
Keywords: Customer relationship marketing; Customer Loyality; Cusomer satisfaction; Banking Indusrty